PENGARUH IMPLEMENTASI MARKETPLACE DAN DIGITALISASI UMKM TERHADAP KESEJAHTERAAN PELAKU UMKM (STUDI KASUS PADA SEKTOR UMKM DI KOTA BANDAR LAMPUNG) - Apip Alansori; Ruli Eko Haryanto; Angelina Faleria; Fadly Muhammad Yahya; Laili May Hanifah (Institut Rahmaniyah Sekayu, 2026)
The purpose of this study is to investigate how marketplace and digitalization affect the welfare of MSMEs in Bandar Lampung City. This research uses a qualitative descriptive methodology and includes in-depth interviews, field observations, and documentation with MSME actors from various industries, including trade, services, and culinary. According to the findings, MSME actors can increase their income, expand market reach, and increase their business awareness by utilizing digital platforms such as Shopee, Tokopedia, and social media. However, the digital transformation process is still hampered by several problems such as low digital literacy, lack of training, poor infrastructure, and lack of funding. By emphasizing not only the economic aspects but also the psychological and social aspects of entrepreneurs' well-being, the study helps in the creation of digitalization strategies for MSMEs. The qualitative techniques used in this study, which provide a more complete picture of the welfare of MSME actors by describing their real experiences and perspectives during the digital transition process, are what make them innovative. Keywords: MSMEs, digitalization, marketplace, welfare, qualitative research